2021
DOI: 10.21608/ejchem.2021.61809.3331
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification and Characterization of Chitosan for Pharmaceutical Applications

Abstract: Nine crosslinked chitosan derivatives (CLCS) were prepared using three different types of crosslinkers: glutaraldehyde, glyoxal and terephthaldehyde. The prepared CLCS were used to control the acyclovir (ACV) release in order to improve its oral bioavailability. The CLCS were prepared by Schiff based reaction and characterized by means of infrared spectroscopy (FTIR), x-ray diffraction measurements, thermogravimetric inspection, differential scanning calorimetry, and scanning electron microscopy (SEM). Establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The respective surface area (26.455, 76.635 and 5.339), pore volume (0.067, 0.219 and 0.010) and pore diameter (3.411, 3.411 and 4.302) values for 3-Phenylpiridine, Nicotine-3-Phenylpiridine and the non-templated, respectively ( Table 2 ), align with the observed presentation except for the pore diameter of the NIP which is more than that of the MIPs. The MIPs are polydisperse as indicated by their different aggregate sizes [ 17 , 18 , 19 , 20 , 21 ], and this is in tandem with the micrographs of the TEM.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The respective surface area (26.455, 76.635 and 5.339), pore volume (0.067, 0.219 and 0.010) and pore diameter (3.411, 3.411 and 4.302) values for 3-Phenylpiridine, Nicotine-3-Phenylpiridine and the non-templated, respectively ( Table 2 ), align with the observed presentation except for the pore diameter of the NIP which is more than that of the MIPs. The MIPs are polydisperse as indicated by their different aggregate sizes [ 17 , 18 , 19 , 20 , 21 ], and this is in tandem with the micrographs of the TEM.…”
Section: Resultsmentioning
confidence: 79%
“…The presence of hydroxyl functionality catalyzes its inherent disposition to swell in the presence of water and makes it challenging for thin film studies to be carried out using it as a matrix. In a bid to overcome these challenges, scientists have adopted approaches like copolymerization and grafting in order to stiffen and restrict the swelling potential, amongst other target goals [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the Mark–Houwink equation was used to calculate the average MW [ 54 ]. The percentage of DDA is calculated from the FTIR spectrum, using this equation: DDA = 100 × (1-(A1655/A3450)/1.33).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-linked CS derivatives (CL-CS) show a pH-adaptive swelling tendency with hindered solubility in their porous structure. The loaded drug can be released from CL-CS by swelling the CS matrix on the gastric acidic pH and drug diffusion through the pores in a sustained release manner [ 54 ]. Drug delivery from polymer systems is influenced by several factors: polymer molecular weight, degree of deacetylation and substitution of polysaccharides, nanoparticle size, and porous structure.…”
Section: Resultsmentioning
confidence: 99%
“…O-Chitosan Schiff Base derivative (Grafted chitosan) Blended with PVA (13-20) were prepared research of characteristics of obtained blends had shown a good level of the miscibility between the PVA and Chitosan that had been shown by FT-IR results of the compound (13), the band broadening in (2400-3600)cm -1 region because of a strong inter-molecular bonding of hydrogen that exists between amino groups of Chitosan and PVA's hydroxyl groups, 1635cm -1 as a result of (C=N) and 1708 cm -1 which meaning C=O ester group 22 , and for the other polymers, the band values are illustrated in table 3. Scanning electron microscope studies (SEM) 23,42 Surface size, morphology, crystallinity and phase locations of created material could all be researched by examining the SEM. The morphology of the surface varies for Grafted Chitosan figure 2 roughness to blend membrane (Grafted chitosan /PVA).…”
Section: Scheme 2 Synthesis Of Polymers [3-4] [9-12]mentioning
confidence: 99%